Sustainable development in the city of Heidelberg - Graczyk, Alicja Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The city of Heidelberg has won twice the price of European Sustainable City Award. The paper presents the latest author’s investigation (July 2014) about the sustainable development in the Heidelberg. The aim of the article is an analyses and assessment of the implementation of sustainable development in the city. The policy and economical instruments implemented at the local level at the very early stage (early 90s) help the city to build ecological education and shape ecological style of life.. The city citizens have a very high level of ecological awareness and very often participate in policy decisions, shaping sustainable development goals of the Heidelberg. The main local priorities for sustainable development are: climate and environment protection, rising energy efficiency by using renewable energy sources, local heat district, ecological transport and building in passive standard.